Economic Discomfort and Wellbeing in Nigeria: Evidence from dynamic ARDL simulation - Ibikunle, Joseph Afolabi; Oyerinola, David Sunday (NIU Journal of Social Sciences, 2022)
The United Nations identified improved health and wellbeing as a major goal in the Sustainable Development Goals in 2015. With less than nine years until the SDGs' deadline, however, unemployment and inflation continue to rise, leaving most citizens living on less than a dollar a day. Theoretical and empirical literature show that there are numerous disadvantages associated with economic discomfort. However, empirical findings on the impact of economic discomfort on wellbeing in Nigeria are virtually non-existent. This study contributes to the misery literature by examining the relationship between economic discomfort and wellbeing in Nigeria. This was achieved through the use of novel dynamic autoregressive-distributed lag simulations and  Breitung and Candelon (2006) frequency domain granger causality test on data covering the period 1991-2020. The study found that economic discomfort has significant negative long run effect on wellbeing in Nigeria. Also, economic discomfort drives wellbeing and no feedback effect in Nigeria. Therefore, Nigerian government should adopt appropriate policies that will help in reducing the high rate of unemployment and inflation to boost public health improvement and in turn bring effective wellbeing to its populace. Keywords: Nigeria, wellbeing, economic discomfort, novel dynamic ARDL simulation.